Epigenetic regulation of Amphiregulin and Epiregulin in colorectal cancer. Issue 3 (7th November 2018) - Bormann, Felix; Stinzing, Sebastian; Tierling, Sascha; Morkel, Markus; Markelova, Maria Rivera; Walter, Jörn; Weichert, Wilko; Roßner, Florian; Kuhn, Natalia; Perner, Juliane; Dietz, Johanna; Ispasanie, Sylvia; et al.
Abstract : Expression of the epidermal growth factor ligands amphiregulin (AREG) and epiregulin (EREG) is positively correlated with a response to EGFR‐targeted therapies in colorectal cancer. Gene‐body methylation sites, which show a strong inverse correlation with AREG and EREG gene expression, were identified in cell lines using targeted 454 FLX‐bisulfite sequencing and SIRPH analyses for AREG/EREG promoters and intragenic CpGs. Upon treatment of colorectal cancer cells with 5‐aza‐2′‐desoxycytidine, methylation decreases at specific intragenic CpGs accompanied by upregulation of AREG and EREG gene expression. The same AREG gene‐body methylation was also found in human colorectal cancer samples and is independent of KRAS and NRAS mutations. Methylation is specifically decreased in the tumor epithelial compartment as compared to stromal tissue and normal epithelium. Investigation of a promoter/enhancer function of the AREG exon 2 region revealed a potential promoter function in reverse orientation. Retrospective comparison of the predictive power of AREG gene‐body methylation versus AREG gene expression using samples from colorectal cancer patients treated with anti‐EGFR inhibitors with complete clinical follow‐up revealed that AREG expression is superior to AREG gene methylation. AREG and EREG genes undergo a complex regulation involving both intragenic methylation and promoter‐dependent control. Abstract : What's new? While epidermal growth factor ligands amphiregulin (AREG) and epiregulin (EREG) are well‐established predictive biomarkers, the regulation of their gene expression in colorectal cancer (CRC) is poorly understood. This study suggests that gene body methylation differentially controls AREG and EREG gene expression, with a complex interplay between DNA methylation‐controlled intragenic regions within the AREG gene and the AREG promoter. Furthermore, gene methylation assessment alone may not be sufficient as an improved predictive marker in combination with KRAS. Patients with KRAS/NRASwt, low AREG expression, and high AREG methylation may potentially benefit from demethylation treatment to increase AREG expression prior to anti‐EGFR therapies.